Towards artificial intelligence-aided MIMO detection for 6G communication systems: A review of current trends, challenges and future directions - Gevira Omondi; Thomas O. Olwal (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
In recent times, artificial intelligence (AI) has gained considerable attention as a highly promising technology for enhancing the performance of multiple-input multiple-output(MIMO) detection in wireless communication networks. AI approaches such as deep learning and reinforcement learning have enabled MIMO receivers to learn and adapt to complex channel conditions and interference scenarios, significantly improving throughput and error rate performance. This study provides a detailed review of the existing status of AI-aided MIMO detection and discusses the potential of this technology for future wireless communication systems, such as 6G. The study also discusses the challenges and opportunities associated with integrating AI techniques into MIMO detection and emphasizes the necessity for additional research in this field.